Immunological Studies on Dermatophytes III. Further Analyses of the Reactivities of Neutral Polysaccharides with Rabbit Antisera to Microsporum quinckeanum, Trichophyton schoenleinii, Trichophyton rubrum, Trichophyton interdigitale, and Trichophyton granulosum - Grappel, Sarah F. (1968)
The serological reactivities of polysaccharides isolated from five species of dermatophytes, Microsporum quinckeanum, Trichophyton granulosum, T. interdigitale, T. rubrum, and T. schoenleinii, with rabbit antisera to these species were studied qualitatively by precipitation in gel and quantitatively by complement-fixation analyses. Significant differences in the serological reactivities of the galactomannans I were detected with antisera to T. schoenleinii and T. interdigitale. The differences appeared to be related to the specificity of these antisera for the galactofuranose residues in the polysaccharides. Antisera to M. quinckeanum, T. granulosum, or T. rubrum did not detect differences between the galactomannans I. The serological reactivities of the galactomannans II were different with each of the five antisera. The reactivities of the glucans could be correlated with the amount of α 1 → 6 linked glucopyranose residues when antisera to T. schoenleinii and M. quinckeanum were used.